Transfer accuracy and precision scoring in planar bone cutting validated with ex vivo data - Milano, Federico Edgardo (2015)
The use of interactive surgical scenarios for virtual preoperative planning of osteotomies has increased in the last 5 years.As it has been reported by several authors, this technology has been used in tumor resection osteotomies, knee osteotomies, and spine surgery with good results. A digital three-dimensional preoperative plan makes possible to quantitatively evaluate the transfer processfrom the virtual plan to the anatomy of the patient. We introduce an exact definition of accuracy and precision of this transfer process for planar bone cutting. We present a method to compute these properties from ex vivo data. We also propose a clinical score to assess the goodness of a cut. A computer simulation is used to characterize the definitions and the data generated by the measurement method. The definitions and method are evaluated in 17 ex vivo planar cuts of tumor resection osteotomies. The results show that the proposed method and definitions are highly correlated with a previous definition of accuracy based in ISO 1101. The score is also evaluated by showing that it distinguishes among different transfer techniques based in its distribution location and shape. The introduced definitions produce acceptable results in cases where the ISO-based definition produce counter intuitive results.